Decision-making of online channels under three power structures. (March 2020) - Jia, Xingxing
In recent years, e-commerce has developed rapidly. Many manufacturers are beginning to integrate with the Internet and regard online platforms, such as online marketplaces and self-owned online malls, as important sale channels for their products. Considering the difference of shopping experience between the two online channels, this paper models price and service competition between the two channels. This paper discusses the decisions of supply chain participants with three power structures, that is, the manufacturer Stackelberg game, the online marketplace firm Stackelberg game, and the Nash game. The results show that the channel service level and the consumer sensitivity to channel service positively affect the channel price and demand. We characterize a threshold for the wholesale price. When the wholesale price is below the threshold, the channel prices are lowest in the Nash game, and when the wholesale price is greater than the threshold, the channel prices are lowest when the manufacture acts as the leader. Differentiated services can improve the supply chain participants' profits and the system's profit compared with the same service. More interestingly, this paper finds that the online marketplace firm should pay attention to improving its service level, while the manufacturer should pay attention to other work differently, such as focusing on generating promotional value and shaping corporate brand image by the self-owned online mall channel.